A Study on the Insulation Property of Electro Porcelain - Gunasekaran, S.; Abitha, P. (Asian Journal of Chemistry, 2010)
The FTIR spectral measurements and the dielectric studies have been carried out for three grades of electro porcelain and for their raw materials. A comparative study of the porcelain samples is carried out with the vibration band assignments and also with dielectric constants in X and K-band frequency ranges. Variation in the absorption of IR radiation and dielectric constant is observed and it may be due to the variation of the percentage of fire clay, which is one of the raw materials used in the preparation of electrical porcelain.